Dual-frequency induction heating for gear hardening: converter, resonant circuit, and FEM modelling - Kierepka, Kamil; Legutko, Piotr; Zimoch, Piotr; Kasprzak, Marcin (IET power electronics, 2018)
In order to achieve required mechanical properties of hardened elements, such as gear wheels, dual-frequency induction heating may be used. Dual-frequency allows heating only the outline of the gear, due to mixed penetration depth of the subject frequencies. This method of hardening requires the process to be very short as heat may spread by means of conduction. This study presents a 3 kW prototype inverter and its control scheme is used to generate dual-frequency output current. The overall efficiency of the inverter is 96%. An analysis of the output resonant circuit is made to find the resonant frequencies. Finally, circuit and finite element method (FEM) simulations are coupled to analyse the effect of dual-frequency current on the magnetic field, current density, and energy density on the surface of a gear wheel.